Clinical and radiographic evaluation of platelet-rich fibrin as an adjunct to bone grafting demineralized freeze-dried bone allograft in intrabony defects - Abhinav Atchuta; Jagadish Reddy Gooty; Vikram Reddy Guntakandla; Sunil Kumar Palakuru; Satyanarayana Durvasula; Rajababu Palaparthy (Wolters Kluwer Medknow Publications, 2020)
Background: Several bone graft materials are popularized in the treatment of intrabony defects. Demineralized freeze-dried bone allograft (DFDBA) is widely used in the treatment of intrabony defects. Platelet-rich fibrin (PRF) is autologous blood preparation which helps in wound healing and regeneration. Hence, this study focuses on evaluation of PRF, DFDBA, and their combination in the regeneration of intrabony defects. Materials and Methods: A total of 39 sites with intrabony defects were randomly assigned into three groups: (Group I - Open flap debridement, Group II - DFDBA alone, and Group III- DFDBA + PRF). Parameters such as probing pocket depth (PPD), relative attachment level (RAL), and radiographic bone fill were measured at baseline, 3 months, and 6 months. Intragroup comparison at various study intervals was made using one-way ANOVA test. Intergroup comparison was made using Tukey's multiple post hoc test. Results: Reduction in the PPD and greater difference in RAL was observed over the study period in all the three groups with greater reduction in DFDBA + PRF group. Reduction in the radiographic defect depths was observed over the study period in all the three groups with the greatest reduction of 38.99% in the DFDBA + PRF group. However, no statistically significant difference was reported by DFDBA versus DFDBA + PRF group. Conclusion: Combination of DFDBA and PRF improved the clinical and radiographic parameters compared to PRF and DFDBA alone. PRF was combined with DFDBA to produce a synergistic effect for treating intrabony defects in chronic periodontitis patients.